A case study - establishing redundant access networks in the telecommunication sector of a developing country - Rahman, Mohammad Ziaur; Pathan, Al-Sakib Khan (2010)
This paper presents a case study on establishing redundant access networks in the telecommunication sector of a developing country. For this work, we have analyzed the conditions of Bangladesh as Bangladesh can be considered as an ideal model among many developing countries for such type of study. We first present the conditions of existing access networks in Bangladesh. Then we compare different access networks in the telecommunications sector and predict the demand for various telecommunication services; such as voice, data, Internet, etc. We also design some possible redundant optical access networks considering some important parameters. Though the economic benefits of having a reliable telecommunication infrastructure are numerous, at present Bangladesh is lagging behind in the deployment of appropriate telecom infrastructure and video and multi-service facilities. For this reason, some basic technical and socioeconomic problems of access network are identified and some recommendations are made considering the prevailing situations. This work may also be useful for working on similar cases in other developing countries like Bangladesh.